New trans dichloro (triphenylphosphine)platinum(II) complexes containing N-(butyl), N-(arylmethyl)amino ligands: Synthesis, cytotoxicity and mechanism of action. Issue 13 (1st July 2016) - Dalla Via, Lisa; García-Argáez, Aída Nelly; Agostinelli, Enzo; Belli Dell'Amico, Daniela; Labella, Luca; Samaritani, Simona
Graphical abstract: Abstract: Some new platinum(II) complexes have been prepared, of general formula trans -[PtCl2 (PPh3 )NH(Bu)CH2 Ar], where the dimension of the Ar residue in the secondary amines has been varied from small phenyl to large pyrenyl group. The obtained complexes, tested in vitro towards a panel of human tumor cell lines showed an interesting antiproliferative effect on both cisplatin-sensitive and -resistant cells. For the most cytotoxic derivative2a the investigation on the mechanism of action highlighted the ability to induce apoptosis on resistant cells and interestingly, to inhibit the catalytic activity of topoisomerase II.